2018
DOI: 10.1530/jme-17-0227
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional signaling underlying endometriosis: current state of knowledge

Abstract: 14Endometriosis is defined as the presence of endometrial tissue outside the uterine cavity. It

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 144 publications
(148 reference statements)
0
25
0
1
Order By: Relevance
“…MALAT1 increase expression of NF-κB which in turn binds with PGE-2 to enhance its expression ( 99 ). PGE-2 activates BCL2/BAX through interaction with EP2/EP4 receptor and suppresses intrinsic apoptotic pathway ( 100 ). PGE2 also activates cell proliferation through EP2/EP3 ( 101 ).…”
Section: Lncrnas and Endometriosismentioning
confidence: 99%
“…MALAT1 increase expression of NF-κB which in turn binds with PGE-2 to enhance its expression ( 99 ). PGE-2 activates BCL2/BAX through interaction with EP2/EP4 receptor and suppresses intrinsic apoptotic pathway ( 100 ). PGE2 also activates cell proliferation through EP2/EP3 ( 101 ).…”
Section: Lncrnas and Endometriosismentioning
confidence: 99%
“…These alterations are summarized in Table 4. Although endometriosis is considered a ‘benign’ disease, it resembles the biologic behavior of malignant cells [113,114], and a change in the expression of various junctional proteins may support the invasive properties of this tissue and may facilitate its growth at ectopic localizations. Moreover, these impairments may also contribute to endometriosis-associated infertility.…”
Section: Direct Cell–cell Interactions In Endometrial Pathophysiologymentioning
confidence: 99%
“…Recent studies have found that repeated cyclical haemorrhage is involved in the initiation and progression of endometriosis via inducing excessive oxidative stress (OS) 2 , which is defined as an imbalance between reactive oxygen species (ROS) and antioxidants 3,4 . Many studies on OS-associated diseases suggest that oxidative balance is complicated and precarious 5 , as ROS not only modifies proteins, impacts lipids, damages DNA strand structure and regulates cell cycle checkpoints 6,7 , but also maintains survival, intensifies adhesion, promotes angiogenesis and facilitates cell cycle progression 810 . In endometriosis, excessive OS results in higher DNA damage and reduced DNA repair activity 3,11 .…”
Section: Introductionmentioning
confidence: 99%